Muons in air showers at the Pierre Auger Observatory: Mean number in highly inclined events - Aab, A.; Asorey, Hernán Gonzalo; Tapia Casanova, Alex Marcelo; Wundheiler, Brian; Allekotte, Ingomar; Mollerach, Maria Silvia; Wahlberg, Hernan Pablo; Platino, Manuel; Figueira, Juan Manuel; Mariazzi, Analisa Gabriela; Gomez Berisso, Mariano; Sciutto, Sergio Juan; et al. (American Physical Society, 2014)
Fil: Aab, A.. Universität Siegen; Alemania